OPTIMALISASI PELAYANAN BALAI PENGAMANAN FASILITAS KESEHATAN DALAM UPAYA MENINGKATKAN MUTU ALAT KESEHATAN DI KOTA SURABAYA - Ningsih, Heri S; Soesiantoro, Adi; Widiyanto, M. Kendry (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2023)
The large number of puskesmas or service facilities that are covered in the BPFK Surabaya work area, are not comparable to medical device testing/calibration institutions in Surabaya, besides that the factor of distance to provinces outside the island is an obstacle that needs to be considered in calibrating medical devices to remote areas and secluded. feel the need to do better planning by paying attention to various aspects of effectiveness and optimizing available resources so that their service activities develop. In Permenkes No. 363 of 1998 that every equipment, especially medical devices that are directly related to humans and are very critical (related to life) must be calibrated to ensure the correctness of the output value and safety or calibration of medical devices, the measuring instruments and standard sizes used must be calibrated periodically also by Referral Testing Institutions such as the Security Center for Health Facilities, LIPI and other private testing. In the medical equipment management cycle, there are medical device maintenance and calibration activities. Medical device maintenance and calibration activities have not run optimally. This is shown by the Application of Facilities, Infrastructure and Medical Devices (ASPAK)